Global Asymptotic Stability of 2-D Digital Filters With a Saturation Operator on the State-Space - Kandanvli, V. Krishna Rao; Kar, Haranath (IEEE transactions on circuits and systems. II, Express briefs, 2020)
This brief investigates the global asymptotic stability (GAS) problem of two-dimensional (2-D) digital filters represented by Roesser model subject to saturation nonlinearities. A new sufficient GAS condition for the underlying 2-D system is derived. The condition is compared with several existing stability conditions.